THE HISTORY OF GYMNASTICS IN THE TERRITORY OF SLOVAKIA FROM 1918 TO 1980 - Michal Babela (University of Ljubljana Press (Založba Univerze v Ljubljani), 2023)
Gymnastics has been practised in the territory of Slovakia for over a century. During this period, Slovak gymnasts have achieved significant sports successes. This manuscript focuses on the emergence and development of gymnastics in the territory of Slovakia from the beginning of the 20th century to the early 1980s, looking at the main reasons and factors that influenced the emergence, development and direction of gymnastics in the territory of Slovakia during this period. The article also features the most successful gymnasts born on the territory of Slovakia who achieved significant sports success at the international level between 1918 and 1980. The basic criterion for including Slovak gymnasts among successful athletes was their representative participation in top international gymnastics competitions, with final placements in all-around and individual gymnastics events, up to a maximum of 10th place. Information detailing the significant achievements of Slovak gymnasts can be found in the attached tables, which list the greatest sports accomplishments of Slovak gymnasts at the Olympic Games, World Championships, and European Championships. Regarding the methodology employed in this manuscript, we adhered to standard historical research methods. Our primary focus was on collecting materials related to the subject matter. We diligently searched for primary sources, including diaries, newspapers, books, speeches, historical records, and electronic data. We then categorized these facts and examined their relationships using the comparative method as our foundation. Based on our analysis of this information, we prepared the manuscript.